HUMAN RESOURCE CAPACITY BUILDING TOWARDS TECHNOLOGY USED FOR BUSINESS SUSTAINABILTY IN THE NEW NORMAL - Tedjokusumo, Edith Primadiana; Devi Rachmasari (Jurnal Bisnis Terapan, 2025)
There are many changes in the business organizations’ perspective and the way of doing the job to achieve the goals of business organization after the Covid-19 pandemic. So, this study aims to find out what problems that may occur in business organization. In addition, it is also important to know from the organization side’s regarding the goals achievement by the role of the employees. Whether the employees are still indeed needed or any other things needed to be added to match with the target of business organization. Another thing that should also be put into consideration is the usage of technology after the pandemic - that could be the only solutions for business organization. The method used here was descriptive qualitative, and the data were taken by the questionnaire and some interviews in a specific manufacture national company in East Java. The result of findings showed the following. After the pandemic, it can be concludes as the usage of technology and applications are beneficial, even though there is some refusal from the employees, but with the assistance and training, the problem is solved; in addition, the production process can run smoothly and the goal of the production can be achieved.